Curing kinetics of phenolphthalein based polyphosphazene towards thermal stability and flame retardancy of polybenzoxazine. Issue 54 (4th October 2019) - Zhao, Ling; Zhao, Chunxia; Wu, Min; Li, Yuntao; Li, Hui; Xiang, Dong; Guo, Cuicui
Abstract : Phenolphthalein type polyphosphazene (PZPT) microspheres were synthesized by an ultrasound assisted precipitation polymerization method, and their structures were confirmed by scanning electron microscopy (SEM) and Fourier transform infrared (FTIR) spectroscopy. Abstract : Phenolphthalein type polyphosphazene (PZPT) microspheres were synthesized by an ultrasound assisted precipitation polymerization method, and their structures were confirmed by scanning electron microscopy (SEM) and Fourier transform infrared (FTIR) spectroscopy. Benzoxazine/PZPT (Ba/PZPT) hybrid materials were fabricated and cured to prepare polybenzoxazine/PZPT (PBa/PZPT) composites. The effects of PZPT microspheres on the curing kinetics and behaviors of Ba were systematically analyzed and supported by differential scanning calorimetry (DSC) and in situ FTIR. The thermogravimetric (TGA) results demonstrated good thermal stability of the PBa composites incorporating PZPT. The peak of heat release rate and total heat release values of PBa/PZPT-5% composites obviously deceased by 57.8% and 17.3% compared to those of the pristine PBa. Moreover, the smoke released from the PZPT/PBa system significantly reduced with the loading of microspheres. Finally, the dynamical mechanical analysis results demonstrated that the T g of PBa flame retardant composites was approximately 210 °C, not affecting further applications of PBa composites.